2022
DOI: 10.1002/cphc.202200098
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Nature of Host‐Guest Interactions in Metal‐Organic Frameworks from a Quantum‐Chemical Perspective

Abstract: Metal-organic frameworks (MOFs) offer a convenient means for capturing, transporting, and releasing small molecules. Their rational design requires an in-depth understanding of the underlying non-covalent host-guest interactions, and the ability to easily and rapidly pre-screen candidate architectures in silico.In this work, we devised a recipe for computing the strength and analysing the nature of the host-guest interactions in MOFs. By assessing a range of density functional theory methods across periodic an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…This issue is addressed by turning to smaller, finite cluster models of the adsorption sites, identified in molecular docking, and treating them at higher levels of theory. While such finite cluster models neglect the periodicity of the MOFs and the guest-guest interactions, they are generally able to accurately capture the local host-guest interactions 16 .…”
Section: Adsorption Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…This issue is addressed by turning to smaller, finite cluster models of the adsorption sites, identified in molecular docking, and treating them at higher levels of theory. While such finite cluster models neglect the periodicity of the MOFs and the guest-guest interactions, they are generally able to accurately capture the local host-guest interactions 16 .…”
Section: Adsorption Geometrymentioning
confidence: 99%
“…We have recently compared cluster and periodic results for two exemplary MOFguest systems, and found that the cluster model is qualitatively able to reproduce the periodic results and is useful to analyse the host-guest interactions. 16 In this work, we transfer the well-established method (and implementation) of molecular docking to the field of MOF-guest complexes. The software AutoDock v4.2.6, originally designed for protein-ligand binding, is used in the initial screening of various adsorption sites of guest molecules inside MOF pores.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently compared cluster and periodic results for two exemplary MOF−guest systems and found that the cluster model is qualitatively able to reproduce the periodic results and is useful to analyze the host−guest interactions. 16 In this work, we applied the method (and implementation) of molecular docking, which is well-established in protein− This new approach is validated by comparing the structures, obtained here via multilevel simulations, to five experimentally determined MOF−guest structures deposited in the Cambridge Structural Database (CSD). We discuss how computational modeling can be used as an efficient tool to elucidate where, in which conformation, and how strongly the guest molecule is adsorbed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although we consider a periodic framework, these features are sufficiently local and can be properly represented with a finite cluster model, which allows for a much broader set of computational tools to be employed. We have recently compared cluster and periodic results for two exemplary MOF–guest systems and found that the cluster model is qualitatively able to reproduce the periodic results and is useful to analyze the host–guest interactions …”
Section: Introductionmentioning
confidence: 99%
“…We have recently compared cluster and periodic results for two exemplary MOF-guest systems, and found that the cluster model is qualitatively able to reproduce the periodic results and is useful to analyse the host-guest interactions. 16 In this work, we applied the method (and implementation) of molecular docking, which is wellestablished in protein-ligand binding, to the field of MOF-guest complexes. The software AutoDock v4.2.6, originally designed for protein-ligand binding, is used in the initial screening of various adsorption sites of guest molecules inside MOF pores.…”
Section: Introductionmentioning
confidence: 99%